Comments on the possibility to interpret functions of human populations from the viewpoint of natural sciences - Henneberg, Maciej (Anthropological Review, 1978)
Starting from the undoubtful statement on the evolutionary origin of man, the author shows the consequences of rigorously extending this line of thought to nowadays human populations. The attempt is made at showing the universal nature of basic ecological and evolutionary laws as tools for the explanation of human activities. The examples used to strengthen some statements concern mainly the ecological interpretation of subsistence strategies and their cultural ramifications, including ideology and art, and feedback relations uniting cultural and genetic mechanisms into one adaptive system with special attention paid to mating systems and the operation of natural selection.